Recovery from Polyglutamine-Induced Neurodegeneration in Conditional SCA1 Transgenic Mice - Zu, Tao (J Neurosci, 2004)
Spinocerebellar ataxia type 1 (SCA1) is an autosomal dominant, polyglutamine-induced neurodegenerative disorder that results in loss of motor coordination caused primarily by a disruption of cerebellar Purkinje cell function. In this study, we developed a conditional SCA1 mouse model to examine whether stopping expression of mutant ataxin-1 alters the disease phenotype. After cessation of SCA1[82Q] transgene expression, mutant ataxin-1, including that in nuclear inclusions, was cleared rapidly from Purkinje cells. At an early stage of disease, Purkinje cell pathology and motor dysfunction were completely reversible. After halting SCA1 expression at later stages of disease, only a partial recovery was seen. Interestingly, restoration of the ability to perform a complex motor task, the accelerating Rotarod, correlated with localization of mGluR1α to the Purkinje cell-parallel fiber synapse. These results show that the progression of SCA1 pathogenesis is dependent on the continuous expression of mutant ataxin-1. Of note, even at a late stage of disease, Purkinje cells retain at least some ability to repair the damage caused by mutant ataxin-1.